(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
every day. Some of us have multiple cell phone devices, numerous types of laptops, smart cars, and many other wireless devices that consume the internet to transmit data from one position to another. The need for so many devices has grown In the present scenario, we consider a new rising technology is known as Fog Technology where the computing takes place at the edge of network which is the advanced version of the cloud computing . The Internet of Things (IoT) represents an innovative world of information and communication technologies for anyone can get connectivity at anyplace at anytime. Fog provides the data, storage, computation and services like the cloud. Paper represents the overview of the Fog computing, applications of fog computing and how it is different from cloud computing. The Fog computing coincides with other forms of rising technology and what impact of this technology will have on the future of information technology.